Beyond Europe: Commentary on Gordon Clark's perspective on financial intermediation. Issue 3 (2nd September 2017) - Sheppard, Eric
ABSTRACT: Gordon Clark assesses the urban and regional infrastructure funding problems created by contemporary developments in the globalization of finance, proposing solutions for the European context. This commentary interrogates the appropriateness of Clark's approach for the Global South. I suggest that Clark's discussion of a global savings glut is embedded in a Euro-American, market-equilibrium-oriented conception of finance. I question the applicability of market-equilibrium thinking in general, and argue that it does not capture the uncertainties, barriers and instabilities associated with accessing finance in the Global South. I also question whether private-sector return-on-investment considerations can finance infrastructure that meets social justice priorities, arguing that it is thus important to assess critically alternative more-than-capitalist finance models for infrastructure provision such as China's Belt and Road initiative.